Design of the licensees on a pedagogical tool: Gibi "pulmão e sua turma" (Research, Society and Development, 2021)
The use and evaluation of alternative pedagogical tools in the construction of knowledge can significantly improve learning. The objective of this research was to analyze through a material previously made, the perception of undergraduate students of the Regional University of Cariri - URCA of the Biological Sciences Course, about the pedagogical tool - Comic "Pulmão and its class". "comics or comics" was used as a possible pedagogical didactic material, a simple and viable method, which can be adapted to various everyday themes, in order to be able to lead the student to a better understanding of the content of the discipline presented during classes. The research was conducted with 154 students regularly enrolled in the Degree course in Biological Sciences of the Regional University of Cariri, CE, Campus Campos Sales-CE and Crato-CE. For the collection of data from the research, a semi-structured questionnaire and the participant's observation were applied. The results indicated that the "comic" as a pedagogical instrument is playful, feasible and practical, in order to be able to lead the student to a better understanding of the content of the discipline; stimulates and motivates the student's curiosity as a teaching methodology, and can be applied to different levels of learning. The proposal seeks to contribute to the reduction and/or overcoming of the difficulties identified in the teaching and learning process.